Quilcapampa : a Wari enclave in Southern Peru - Jennings, Justin; Yépez Álvarez, Willy, 1969-; Bautista, Stefanie L. (University Press of Florida, 2021)
"Analyzing evidence from the site of Quilcapampa in the Sihuas Valley of Southern Peru, contributors to this volume discuss the ninth-century settlement's relationship to the broader Wari empire and reimagine the empire's role in the widespread changes of the Andean Middle Horizon period"--